Redescription of the last instar larva of Stenophylax fissus (McLachlan 1875) and the DNA barcode of Stenophylax crossotus McLachlan 1884 (Trichoptera: Limnephilidae) with an updated diagnostic matrix of the known larvae of Stenophylax species of the Iberian Peninsula - Ruiz-García, Antonio; Garzón, Andrés; Zamora-Muñoz, Carmen (Zootaxa, 2021)
The larva of Stenophylax fissus (McLachlan 1875) is redescribed, illustrated, and compared with morphologically similar Limnephilidae larvae from the Iberian Peninsula. In addition, the sequence of the mtCOI gene in the barcode region of one individual is reported. Likewise, the barcode and the conspecificity between two larvae and one female of the non-sequenced species S. crossotus are given. In addition, the high genetic diversity among S. sequax populations is highlighted, suggesting a complex of cryptic species. Finally, a diagnostic matrix of the known larvae of Stenophylax species from the Iberian Peninsula is provided.